The economic nature of crisis phenomena in the activities of construction enterprises: sources, phases, and organizational-structural manifestations - SIEDINKIN , Oleksandr (Ways to Improve Construction Efficiency, 2025)
The economic nature of crisis phenomena in construction enterprises encompasses a systemic set of factors that shape the instability of their production, financial, and organizational structures. Crisis processes arise not only as a result of macroeconomic fluctuations or financial disruptions but also as reflections of internal dysfunctions that accumulate within the enterprise management system. Their sources have a multilevel nature – ranging from institutional and industry-level factors to intra-organizational causes. It is precisely this multidimensionality that determines the complexity of forecasting and overcoming crises. The construction industry, due to its capital intensity, project duration, and dependence on external financing, is particularly vulnerable to crisis disturbances. Any change in resource costs, tax conditions, or regulatory frameworks can transform into systemic deviations affecting all levels of enterprise activity. At the same time, internal factors – inefficient management, overloaded structures, and the absence of adaptive strategies – can turn temporary instability into a deep organizational crisis. The economic nature of crisis phenomena is defined by imbalances between expenditures and revenues, resources and needs, strategic objectives and operational decisions. Each phase of crisis development – from latent to acute and chronic – is accompanied by characteristic changes in managerial behavior, communication patterns, and power structures. External shocks (inflation, military actions, declining investment activity) intensify internal contradictions, which manifest as financial deficits, staff outflow, and violations of executive discipline. The organizational and structural manifestations of a crisis are expressed through the loss of functional integrity, weakened control, interdepartmental conflicts, and the breakdown of horizontal links. In the final phase, administrative paralysis occurs, leading to a loss of manageability. However, it is precisely at this stage that mechanisms of anti-crisis renewal may emerge – restructuring, digitalization of management, and the implementation of risk-oriented strategies.